2004
DOI: 10.1021/es049800q
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury and Total Mercury in Plant Litter Decomposing in Upland Forests and Flooded Landscapes

Abstract: The overall objectives of this study were to examine the effects of flooding on the decomposition and mercury (Hg) content of tissues from plants common to boreal upland forests at the Experimental Lakes Area in northwestern Ontario. We used litterbags to study changes in total Hg (THg), methyl Hg (MeHg), carbon (C), and nitrogen (N) in 12 different plant tissues (birch, alder, blueberry, and Labrador tea leaves, bunchberry plants, jack pine needles, Sphagnum spp., Polytrichum spp., and Pleurozium spp. bryophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 52 publications
9
108
0
2
Order By: Relevance
“…4), suggesting common sources for the two species. At Sleepers we have inferred that near-stream or in-stream particulate organic matter, mobilized during storms (Hall and St. Louis, 2004), is the common source for THg and MeHg (Schuster et al, 2008). Mobilization of particulate organic matter is also a plausible mechanism at Panola, where in-stream sediment is high in organic matter, and at Icacos, where bed sediment and suspended sediment are low in organic matter but there is a high correlation of THg and POC (see below).…”
Section: Episodic Transportmentioning
confidence: 96%
“…4), suggesting common sources for the two species. At Sleepers we have inferred that near-stream or in-stream particulate organic matter, mobilized during storms (Hall and St. Louis, 2004), is the common source for THg and MeHg (Schuster et al, 2008). Mobilization of particulate organic matter is also a plausible mechanism at Panola, where in-stream sediment is high in organic matter, and at Icacos, where bed sediment and suspended sediment are low in organic matter but there is a high correlation of THg and POC (see below).…”
Section: Episodic Transportmentioning
confidence: 96%
“…1), show that sampling replications and time of exposure (i.e., 18 months) yielded substantial and detectable mass losses during the laboratory incubation study. Rates of mass decreases were different among litter species, and aspen leaf litter showed the strongest dry mass decrease (31 % after 18 months) while pine litter showed only small losses (8 % coniferous litter (Kaneko and Salamanca, 1999;Hall and St. Louis, 2004), while others found the opposite (Demers et al, 2007). Some studies observed inconsistent trends or time-dependent trends, e.g., where initial differences between litter species disappeared during longer time periods (Moore et al, 1999;Sundarapandian and Swamy, 1999;Prescott et al, 2000).…”
Section: Changes In Dry Mass As Well As Concentration and Mass Changementioning
confidence: 99%
“…As a result, field observations generally show strong Hg enhancement in surface litter and soil organic C fractions, greatly exceeding Hg concentrations of the original plant detritus inputs (Lindberg and Harris, 1974;Nater and Grigal, 1992;Hall and St. Louis, 2004;Demers et al, 2007;Tsui et al, 2008;Obrist et al, 2011). Continued sorption of atmospheric Hg to litter and soil organic C pools in the field, however, complicates the study of fate of Hg associated with litter and soil organic C, as newly sorbed Hg is difficult to separate from Hg originally associated with plant tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Similar, Friedli et al (2007) reported surface litter levels between 68 and 127 µg kg −1 in a boreal forest site in Canada and higher Hg contents in organic layers (100 to 250 µg kg −1 ), andÅkerblom et al (2008) reported higher Hg/C ratios in the lower half of forest mor layers as compared to the upper half in boreal forest sites. Hall and St. Louis (2004) reported total Hg mass increases in decomposing boreal forest leaves and needles during an 800 day in situ decomposition study using litter bags along with decreases in C and N. Åkerblom et al (2008) attributed this trend to a natural downward enrichment of Hg due to soil decomposition or other processes, and Grigal (2003) similarly concluded that a higher Hg density of organic matter in the mineral soil as compared to the forest floor implies that less Hg than C is lost during OM mineralization. Similar enrichment of Hg in plant detritus was first reported for aquatic ecosystems by Lindberg and Harriss (1974).…”
Section: Trends In Leaf and Litter Hg Concentrations And Stochiometrymentioning
confidence: 99%